PENGARUH BOPO DAN LDR TERHADAP KINERJA KEUANGAN PADA BANK UMUM KONVENSIONAL PERIODE 2017-2019 - Tirey Widya Pamungkas; Gusganda Suria Manda (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2021)
The purpose of this study was to determine the effect of operational risk as proxied by BOPO and liquidity risk as proxied by LDR on financial performance as proxied by ROA. The object of this research is 10 conventional commercial banks for the 2017-2019 period. The analytical method used is descriptive quantitative analysis, multiple linear regression analysis and classical assumption test. The results in this study are operational risk (BOPO) partially has a negative effect on financial performance (ROA) and liquidity risk (LDR) partially has no effect on financial performance (ROA). As well as operational risk (BOPO) and liquidity risk (LDR) simultaneously affect financial performance.